Design of Quadcopter Robot as a Disaster Environment Remote Monitor - Made Sudarma; I.B. Alit Swamardika; Adinata Mas Pratama (Institute of Advanced Engineering and Science, 2016)
As technology development increase, human more use robot technology to help in many fields. One of robot technology advances is the flying robot Quadcopter. The quadcopter robot is an Unmanned Aerial Vehicle or UAV that consists of four propellers and four brushless motors that function as actuator. Quadcopter was designed by using KK Board V 2.0 Flight Controller which is a series of motor rotation controller and all at once has Accelerometer censor as acceleration censor and Gyroscop censor as a balance or stability censor. The robot controlling is by using remote control (RC), and GoPro HD Hero2 camera was installed to monitor the condition of the environment. Result of testing is that the quadcopter has maximum load for 4.4 kg and maximum range distance of RC is 100 meters without any barrier and 50 meters with barrier. In the testing, robot can fly with maximum height for 30 meters from land surface. The robot is equipped with camera, so the quadcopter flying robot can be used to monitor any places that are hard to reach.